Partial greater trochanter osteotomy for hip reduction in total hip arthroplasty for high dislocated hip: a preliminary report - Liu, Rui Yu (BioMed Central, 2014)
BACKGROUND: Hip reduction in total hip arthroplasty for high dislocated hips is difficult. Various femur osteotomy procedures have been used for hip reduction, but these methods increase operative time and risk of nonunion. We investigated the efficacy of a novel partial greater trochanter osteotomy technique for hip reduction in total hip arthroplasty for patients with high hip dislocation. METHODS: Twenty-one patients (23 hips) with high dislocated hip were treated with total hip arthroplasty that included partial greater trochanter osteotomy, i.e., the upper 2/3 greater trochanter was resected, and the gluteus medius muscle attachment was spared. The clinical outcome was evaluated by comparing the Harris hip scores and radiographic exam results, obtained before surgery and at follow-ups. RESULTS: Follow-ups of 21 patients ranged from 13 to 56 months. The mean Harris hip score increased from preoperative 55.0 (36–69) to postoperative 86.1 (71–93; P = 0.00). The average preoperative leg length discrepancy in patients with unilateral high hip dislocation was 46 mm (28–65 mm); postoperatively leg length discrepancy was less than 1 cm in 11 patients, between 1 and 2 cm in 8 patients, and more than 2 cm in 2 patients. The average leg lengthening at the time of surgery was 36 mm (24–54 mm). Trendelenburg’s gait changed from positive to negative in 20 hips by the last follow-up. No nerve injury occurred postoperative. CONCLUSION: Partial greater trochanter osteotomy is an effective method to render hip reduction in total hip arthroplasty for patients with high dislocation of the hip. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2474-15-293) contains supplementary material, which is available to authorized users.